Combined application of wounding stress and extrusion as an innovative tool to obtain carrot powders with modified functional properties. Issue 1 (1st January 2019) - Viacava, Fernando; Santana-Gálvez, Jesús; Heredia-Olea, Erick; Pérez-Carrillo, Esther; Jacobo-Velázquez, Daniel A.
ABSTRACT: Wounding stress induces the accumulation of phenolics in carrots. However, its effect on cell-wall constituents has not been studied. Extrusion generates modifications in high-fiber food matrices. In this study, the combined effect of wounding stress and extrusion on cell-wall constituents and functional properties of carrots was evaluated. Wounding stress was applied by shredding carrots and storing the tissue (48 h/15°C). The stressed tissue (wounding stress carrot, WSC) was dehydrated and then extruded at temperature, 60 or 100°C, and screw configuration, continuous or expansion. Extrudates were milled and analyzed for cell-wall constituents and other physicochemical parameters. Cellulose content increased (112%) as a response to wounding. Furthermore, extrudates obtained from WSC showed higher content of cell-wall components. For instance, insoluble and total lignin content increased (54–84%) with extrusion conditions. Furthermore, WSC showed higher oil absorption index and lower water solubility index (WSI); whereas extrudates showed the highest WSI.